CHANGES IN PHYSICAL PROPERTIES OF THE MESH OF TRAMMEL NET POST FISHERMAN OPERATION IN TIKU V JORONG TANJUNG MUTIARA DISTRICT AGAM REGENCY - Yanti. E, Wisnove; Nofrizal, Nofrizal; Isnaniah, Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe research was conducted in March-April 2018 which was held in Nagari Tiku V Jorong, Tanjung Mutiara Subdistrict, Agam Regency. The goal of theresearch was to see the changes in the physical properties of the mesh on the trammel net post-operation fishing gear that is after being used for 0, 1 month, 6 months and 12 months, so that the trammel net fishing gear net is known. The method used in this study is the survey method which is to collect data and materials at the research location, then proceed with a direct experiment method or experiment in the laboratory of the Department of Fisheries Resource Utilization, Riau University. The results of this research indicate that the breaking load on the net both inner net and outer net has decreased over time, this can be seen with the BL equation (Breaking Load) = -0.0044 t + 0.1974 for the inner net and BL (Breaking Load) = -0.0231t + 0.7547 for the outer net. In the elongation value also decreased with the equation E (elongation) = -2.8816t + 26.117 for inner net and E (elongation) = -1.6231t + 54.01 for the outer net. Increased use of age causes the size of the mesh to increase but not drastically. Whereas for node stability there is no node shift because the net breaks at the foot of the thread instead of the loose node. Based on this study it can be concluded that the technical age of the net is 12 months. Keywords : mesh size, physical properties, trammel net, usage age.